Modern and future forestry based on biotechnology - Shihui Niu; Jihua Ding; Changzheng Xu; Jing Wang (Modern Agriculture)
Abstract Forest is the most important terrestrial component of the Earth's biosphere, containing nearly 80% of terrestrial biodiversity. However, climate change and population growth are exacerbating deforestation and forest degradation. Reforestation efforts aim to restore ecosystems, but the effectiveness of traditional tree plantations in repairing the ecological function of native forests is controversial. The ideal scenario for forestry in the future is to meet the growing demand for forest products while keeping forest sustainable development. One possible way forward is to greatly improve the productivity and adaptability of forests through molecular breeding to use fewer Short Rotation Intensive Culture (SRIC) plantations to produce sufficient forest products. In the last 2 decades, advances in biotechnologies such as high‐throughput sequencing and genome editing are transforming tree breeding and forestry. Here, we propose possible future directions for modern forestry, including molecular design tree breeding, agroforestry and mixed farming, sustainable and biosphere friendly forestry.